The application of optical technology in the diagnosis and therapy of oxidative stress-mediated hepatic ischemia-reperfusion injury - Wang, Lijuan; Shao, Jiali; Su, Chen; Yang, Jinfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatic ischemia-reperfusion injury (HIRI) is defined as liver tissue damage and cell death caused by reperfusion during liver transplantation or hepatectomy. Oxidative stress is one of the important mechanisms of HIRI. Studies have shown that the incidence of HIRI is very high, however, the number of patients who can get timely and efficient treatment is small. The reason is not hard to explain that invasive ways of detection and lack of timely of diagnostic methods. Hence, a new detection method is urgently needed in clinic application. Reactive oxygen species (ROS), which are markers of oxidative stress in the liver, could be detected by optical imaging and offer timely and effective noninvasive diagnosis and monitoring. Optical imaging could become the most potential tool of diagnosis of HIRI in the future. In addition, optical technology can also be used in disease treatment. It found that optical therapy has the function of anti-oxidative stress. Consequently, it has possibility to treat HIRI caused by oxidative stress. In this review, we mainly summarized the application and prospect of optical techniques in oxidative stress-induced by HIRI.